2010
DOI: 10.1021/bi902005t
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-like Interaction of Congo Red with the Amyloid β Peptide

Abstract: Accumulating evidence links prefibrillar oligomeric species of the amyloid beta peptide (Abeta) to cellular toxicity in Alzheimer's disease, potentially via disruption of biological membranes. Congo red (CR) affects protein aggregation. It is known to self-associate into micelle-like assemblies but still reduces the toxicity of Abeta aggregates in cell cultures and model organisms. We show here that CR interacts with Abeta(1-40) in a manner similar to that of anionic detergents. Although CR promotes beta sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
97
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 24 publications
13
97
1
Order By: Relevance
“…This feature, in addition to its small molecular size and ease of penetration of the blood-brain barrier, make congo red useful as a molecular probe for both the antemortem and in vivo visualization and quantification of brain amyloid [1,2,5,6] . Interestingly, emerging studies demon- [4,9] . It has been reported that congo red is able to block Aβ aggregation and toxicity in rat hippocampal neuron culture [20] , HeLa and PC12 cells and in human macrophage culture [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature, in addition to its small molecular size and ease of penetration of the blood-brain barrier, make congo red useful as a molecular probe for both the antemortem and in vivo visualization and quantification of brain amyloid [1,2,5,6] . Interestingly, emerging studies demon- [4,9] . It has been reported that congo red is able to block Aβ aggregation and toxicity in rat hippocampal neuron culture [20] , HeLa and PC12 cells and in human macrophage culture [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Congo red is a secondary diazo dye that is usually used as an indicator for the presence of amyloid fibrils and is one of the model compounds that has been extensively studied for its interaction with amyloid beta peptide (Aβ) [1][2][3][4][5] . In addition, it has been found that congo red can block Aβ-formed ion channels [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the degree of packing and the protein's intrinsic stability it also depends -as remarked above -upon function-related conformational rearrangement [35,36,38,39].…”
Section: Structural Adaptability Of Molecules Forming Supramolecular mentioning
confidence: 99%
“…In some cases, however, even a tightly packed protein may -when binding its natural target ligand -undergo sufficient structural rearrangement to permit penetration of additional large supramolecular ligands penetrating outside of the primary binding site. This type of interaction, while temporary, often drastically modifies the function of the protein [35,36].…”
mentioning
confidence: 99%
“…The complexation of CR with amyloids is the subject of numerous studies [29][30][31]. The problem is difficult and its molecular underpinnings remain speculative, since CR itself is not visualized under electron microscopy, while amyloids -despite their ordered structure -do not attain the necessary level of crystallization order.…”
Section: Insertion Of Metal Ions Into Proteins By Supramolecular Ligandsmentioning
confidence: 99%